2019 IEEE/CVF International Conference on Computer Vision Workshop (ICCVW) 2019
DOI: 10.1109/iccvw.2019.00246
|View full text |Cite
|
Sign up to set email alerts
|

GCNet: Non-Local Networks Meet Squeeze-Excitation Networks and Beyond

Abstract: The Non-Local Network (NLNet) presents a pioneering approach for capturing long-range dependencies, via aggregating query-specific global context to each query position. However, through a rigorous empirical analysis, we have found that the global contexts modeled by non-local network are almost the same for different query positions within an image. In this paper, we take advantage of this finding to create a simplified network based on a queryindependent formulation, which maintains the accuracy of NLNet but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
891
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 1,655 publications
(894 citation statements)
references
References 46 publications
3
891
0
Order By: Relevance
“…Attention-based global context modelling has been successfully applied in various visual recognition applications such as semantic segmentation [43], panoptic segmentation [23], video classification [35], generative adversarial networks [44], and representation learning [4,17,17,22,29,37,11]. It is recently reported that the non-local pixel-wise attention can be simpli- fied as a more memory-efficient query-independent attention without sacrificing performance [35,4]. Following this work, UPI-Net models the global context of placental ultrasound images via lightweight non-local heads and semantic enhancement heads without introducing a large amount of network parameters or computational overhead.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Attention-based global context modelling has been successfully applied in various visual recognition applications such as semantic segmentation [43], panoptic segmentation [23], video classification [35], generative adversarial networks [44], and representation learning [4,17,17,22,29,37,11]. It is recently reported that the non-local pixel-wise attention can be simpli- fied as a more memory-efficient query-independent attention without sacrificing performance [35,4]. Following this work, UPI-Net models the global context of placental ultrasound images via lightweight non-local heads and semantic enhancement heads without introducing a large amount of network parameters or computational overhead.…”
Section: Related Workmentioning
confidence: 99%
“…Our proposed UPI-Net ( Fig. 4) aims to address these potential issues by adding two types of feature refinement blocks in a nested deep architecture: (i) global context (GC) blocks [4]; (ii) convolutional group-wise enhancement (CGE) blocks. A GC block modulates low-level features via simplified non-local operations and channel recalibration operations.…”
Section: Network Architecturementioning
confidence: 99%
See 3 more Smart Citations